History And Development of Pedagogical Theory (Journal of Pedagogical Inventions and Practices, 2023)
In this article, we can have complete information about the history of the theory of pedagogy and the period of its development. It is to reveal the theoretical and methodological foundations of the science of pedagogy, to achieve their in-depth assimilation by young pedagogues, to form the skills and qualifications of students to successfully organize pedagogical activities